2007
DOI: 10.1088/0957-4484/18/32/325604
|View full text |Cite
|
Sign up to set email alerts
|

Structural and luminescence investigation on gadolinium gallium garnet nanocrystalline powders prepared by solution combustion synthesis

Abstract: Nanocrystalline powders of undoped and lanthanide (Pr 3+ , Tm 3+ )-doped gadolinium gallium garnet, Gd 3 Ga 5 O 12 (GGG), were prepared by propellant synthesis and studied by x-ray powder diffraction (XRD), electron diffraction (ED), high-resolution electron microscopy (HREM) and luminescence spectroscopy. The x-ray diffraction patterns of the GGG samples were analysed using the Rietveld method. The Rietveld refinement reveals the existence of two garnet-type phases: both are cubic (space group I a3d) with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 53 publications
5
32
0
Order By: Relevance
“…The effective decay time of the 1 D 2 level, obtained from equation (2), results to be 37.2 μs. This value is similar to that found for a Tm 3+ -doped GGG nanocrystalline sample prepared by a combustion procedure [6]. [55], while the YAG and GGG samples have been prepared with a propellant technique [42] and a citric acid solgel procedure [54], respectively.…”
Section: T Msupporting
confidence: 82%
See 2 more Smart Citations
“…The effective decay time of the 1 D 2 level, obtained from equation (2), results to be 37.2 μs. This value is similar to that found for a Tm 3+ -doped GGG nanocrystalline sample prepared by a combustion procedure [6]. [55], while the YAG and GGG samples have been prepared with a propellant technique [42] and a citric acid solgel procedure [54], respectively.…”
Section: T Msupporting
confidence: 82%
“…It has been found that nanosized materials can maintain excellent spectroscopic properties typical of bulk systems, making them interesting as materials for devices of technological importance, especially in the photonic and bioimaging fields [1][2][3][4][5]. Among oxidebased materials, garnets have gained a considerable degree of attention due to their interesting chemical and physical properties such as high density, high thermal conductivity and hardness, and good chemical stability [6]. Many investigations on the luminescence properties of lanthanidedoped garnets have shown that they can be usefully employed as laser crystals, phosphors and upconverter materials [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Y 3 Al 5 O 12 (YAG) 3,4 and the Gd 3 Ga 5 O 12 (GGG) 5,6 nanostructures have proved to be efficient, flexible, and robust luminescent materials which can support high concentrations of RE 3þ ions through substitution of Y 3þ or Gd 3þ ions without charge compensation. Y 3 Ga 5 O 12 (YGG) is also a good host matrix for rare earths; thus, it is worth researching its structural and electronic properties under high pressure which can provide important information about how a change in the RE 3þ environment would affect its luminescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…It has been a subject of intense research for the past three decades, because it is a very good host for doping with rare-earth ions [2]. Various authors [3][4][5][6] have studied the luminescence properties of GGG crystals doped with lanthanide ions.…”
Section: Introductionmentioning
confidence: 99%